PENGELOMPOKAN PERLOMBAAN KSN (KOMPETISI SAINS NASIONAL) JENJANG SMP BERDASARKAN CABANG LOMBA MENGGUNAKAN METODE CLUSTERING (STUDI KASUS : DINAS PENDIDIKAN KAB.LANGKAT) - Andi Sukarlin; Budi Serasi Ginting; Imeldawaty Gultom (JSIK (Jurnal Sistem Informasi Kaputama), 2021)
To get the KSN competition (National Science competition) grouping application contained in the data archive, the Education Office needs to have a competition grouping data system that has a structured and clear procedure that is in accordance with the vision, mission and strategy. Because in the KSN data competition that was taking place, data was only inputted manually. So here I want to make a Grouping Application to see the grouping data of the KSN competition based on the competition branch, school and district origin, it is necessary to do the application for the design of the KSN competition grouping data system. Tests carried out using the clustering method with the K-Means algorithm, it can be seen that the KSN competition group, the competition branch, from the school and the sub-district which only has the highest group and appears most frequently in the KSN competition grouping.